From Antiquity to Abstraction: A Content and Semiotic Analysis of Athens Epidaurus Festival Posters, 1955–2025 - Panayi, Andreas (My University, 2022)
he festival poster is a ‘semiotic mirror’, reflecting not only its visual identity but also the signs that define its vision and meaning to the public. The current paper examines 128 posters of the Athens Epidaurus Festival (AEF), published between 1955 and 2025, as a case study to explore their role and contribution to the construction of the Festival’s identity, and nation branding of Greece through cultural heritage and graphic design. The conceptual framework of this study draws on theories of nation branding, cultural heritage, social semiotics, graphic and visual communication, and examines how poster design contributes to the branding of a nation, and specifically Greece. Using quantitative content analysis, both verbal (textual) and nonverbal (visual) signs of the posters are systematically examined to identify the common themes, mediums, and dominant colours, among others. By applying a semiotic analysis on specific posters, the findings reveal that the graphic design language of the corpus balances, strategically, tradition and innovation, aligning the festival with both its historical roots and its contemporary cultural role. Consequently, the analysis indicates a clear shift in the festival’s visualisation and branding—most notably after its separation from the Greek National Tourism Organisation in 1998—when designs moved from reliance on monumental antiquities and ancient Greek imagery toward more abstract, symbolic, and cosmopolitan visual languages.
Keywords: Semiotics, Typography, Graphic Design, Posters